MicroRNAs as Key Regulators of Ovarian Cancers. (5th September 2019) - Satapathy, Sandeep; Kumar, Chanchal; Singh, Roshan Kumar
The tumor microenvironment can be realistically viewed as an active battle ground between the host immune system and the growing tumor cells. This reactive space surrounding the tumor possesses several possibilities and facilitates the progression of a tumor from a neoplastic stage to that of metastasis. The contemporary approach of understanding the cancer biology from a "within the cell" perspective has been largely challenged with complex and intricate "outside the cell" events. Thus understanding the biology of the tumor microenvironment has been of scientific and clinical interest. Small non-coding microRNAs with a pleotropic and wide range of cellular gene targets can be reasonably hypothesized to regulate the events of carcinogenesis and progression. MicroRNAs have been investigated in different cancer models, and evidence of their involvement in the regulation of the tumor microenvironment has been of much interest. In particular, a major interest has been exploring the role of the tumor microenvironment in regulating the interaction of cancer cells with surrounding stromal components and the effect of such interactions on the cancer cells. Fine-tuned regulation by these microRNAs extends our contemporary understanding of these small biomolecules in epigenetic regulations. This review focuses on microRNAs that are dysregulated in ovarian carcinomas, their effect on the components of the tumor microenvironment, and the correlation of their heterogeneous expression profiles with disease severity and prognosis in patients. In addition, this paper also discusses the differential expression of exosomal microRNAs that are known to link the cancer cell with its microenvironment, facilitating the development of an improved prognostic/diagnostic marker and effective therapeutic regime.